2021
DOI: 10.1093/jas/skab366
|View full text |Cite
|
Sign up to set email alerts
|

Intake, ruminal fermentation parameters, and apparent total-tract digestibility by beef steers consuming Pensacola bahiagrass hay treated with calcium oxide

Abstract: To determine the effect of CaO treated Pensacola bahiagrass (Paspalum notatum) hay on intake, ruminal fermentation parameters, and apparent total tract digestibility of nutrients, 9 ruminally cannulated Angus-crossbred steers were used in a triplicated 3 × 3 Latin square design. Steers had ad libitum access to either: 1) untreated dry hay (DH;  n = 8); 2) hay at 50% DM treated with 8.9% CaCO3 [dry matter (DM) basis; CC; n = 9]; or 3) hay at 50% DM treated with 5% CaO (DM basis; CO; n = 8). Water was added to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The in vitro culture has become a commonly used technique due to its high correlation with in vivo digestibility and ease of operation. Importantly, in vitro degradation is one of the most direct indicators to evaluate feed quality, which not only reflects the utilization status of nutrients but also evaluates the effect of pretreatment (Ciriaco et al, 2021 ). The chemical composition of forage affects digestibility, and generally high CP and low plant cell wall content are beneficial to improving DM digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro culture has become a commonly used technique due to its high correlation with in vivo digestibility and ease of operation. Importantly, in vitro degradation is one of the most direct indicators to evaluate feed quality, which not only reflects the utilization status of nutrients but also evaluates the effect of pretreatment (Ciriaco et al, 2021 ). The chemical composition of forage affects digestibility, and generally high CP and low plant cell wall content are beneficial to improving DM digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the methods have not been widely accepted by farmers due to their high processing costs, unsatisfying effectiveness, and environmental concerns [7]. According to a published study, CaO compared to other chemical reagents like NaOH presents lesser health risks and is easier to handle [8]. Recent studies have demonstrated the potential of anaerobic CaO alkalization in improving the nutritive value of crop residues and other roughages [9,10].…”
Section: Introductionmentioning
confidence: 99%